Resolution of Visual Snow Syndrome Symptoms Through NeuroOptometric Rehabilitation, Chromatic Filters, and Syntonic Phototherapy: A Case Report. - DeStefano, Michael (Optometry & Visual Performance, 2026)
Background: Visual snow syndrome is a neurological disorder comprising an array of visual and non-visual symptoms, the hallmark symptom being the perception of static-like dots covering the entire visual field. Interest in and awareness of visual snow syndrome have grown considerably in recent years. Case Report: This case focuses on a 17-yearold male patient who initially presented with complaints related to reading. Examination uncovered binocular vision and oculomotor difficulties. He had a history of coexisting attentiondeficit hyperactivity disorder, past psychological and physical abuse at school, and constant anxiety. He also confirmed an array of visual and neurological symptoms that he had not known were abnormal: static in his vision, palinopsia, afterimages, and tinnitus, among others. Syntonic phototherapy intervention eliminated the patient’s feelings of anxiety and inattentiveness, while a chromatic filter eliminated his visual disturbances. Adding low amounts of ambient prism eliminated his motion sensitivity; the patient was then prescribed glasses containing that filter and prism combination. He then completed a vision therapy program. By the end of the program, his visual disturbances, attention difficulties, and anxiety were gone, even when not wearing his glasses. Conclusions: This case report demonstrates that, while people with visual snow syndrome may often respond differently to various treatments, visual snow syndrome is, in fact, possible to eliminate. Furthermore, it reflects the potential of nonpharmacological interventions, such as chromatic filters and syntonic phototherapy, to improve mental functions such as mood and attention.